Technology Entrepreneurship Project (ENT 600) : Khind Holdings Berhad / Mohamad Jiwa Zulkifli - Zulkifli, Mohamad Jiwa (2021)
Khind Holdings Berhad is a company that produces various types of home appliances and electrical products. Khind Holdings Berhad is a public trading company founded by Cheng King Fa in 1961. It is located in Selangor, Malaysia. One of the products produced by Khind company is Khind fan. A fan is an electrical device that helps reduce heat and provide comfort. There are several types of fans produced by this company namely box fan, table fan, and standing fan. The objective of this study is to analyze the problems faced by Syarikat Khind Holdings Berhad and provide better solutions and solve problems and give suggestions to companies in order to improve their company in the future. After doing company analysis, there are some issues that are based on Khind Slim Box Fan. The problem is no airflows control, the second is the noise problem that affects the user. The third problem is the fragile body that is not durable. Therefore, this study was released with three alternatives. The first alternative is to produce airflows control and remote-control technology. Box fan using airflows control and remote-control technology can help control wind direction and easy to ON / OFF and control the speed. The second alternative is to modify or use motor gear technology from WEG Austria. Renewable box fan or using this gear motor can less noise and save energy efficiency. The last alternative is to improve plastic thickness technology. The box fan updated with plastic technology is able to make the body part of the slim box fan will be more durable. Therefore, this study came out with a proposal to choose one of the alternatives. This study proposes to choose to produce making airflows and remote-control technology. This is because the function of airflows is to you can easily adjust the fan up and down to get the air right where direction you want it. It also easy to turn on or turn off the fan and control the speed of box fan.